ANALISIS BUTIR SOAL SUMATIF SEMESTER GANJIL MATA PELAJARAN FISIKA - Umacina, Nurlaila Eka Putri; Mandolang, Aswin H.; Rondonuwu, Inneke T. (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
This study aims to determine the quality of odd semester summative items in physics in terms of validity, reliability, distinguishing features, difficulty levels, trick effectiveness, and questions categorized as LOTS and HOTS. This research is a descriptive study with a quantitative approach. Data collection techniques in this study are documentation. The data obtained were analyzed and calculated manually using Microsoft Excel and Anates. From the results of this study indicate the quality of summative items physics subjects Natural Sciences in SMA Negeri 1 Remboken known problem description 1 item number has good quality, 3 item numbers have medium quality, 1 item number has a bad quality and obtained 100% of questions categorized LOTS. the quality of summative items in physics subject at SMA Negeri 2 Tondano for multiple choice questions, there are 8 numbers that have good quality, 7 questions that have medium quality, 10 numbers that have poor quality. For the description of the questions there are 2 numbers of questions that have very good quality, 1 number of questions has good quality, 2 numbers of questions have medium quality and obtained 94% of the questions are categorized LOTS and 6% of questions are categorized as HOTS.